Airway Stent in Lung Cancer: A Narrative Literature Review - Jeffri Sofian Leksana; Oea Khairsyaf; Afriani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Lung cancer complications are the leading cause of death in lung cancer patients. This study aimed to describe the prevalence of stent placement, indications for stent placement, success and complication rates, and prognosis of airway stent placement in patients with lung cancer. Malignant central airway obstruction (MCAO) is one of the significant complications. Insertion of airway stent can restore airway patency in more than 90% of patients with MCAO. Airway stent placement is indicated in patients with extrinsic lesions, obstruction of ≥ 50%, have patent airway below the obstruction, and are not in the terminal state. The technical success was reported to be very high and consistent with the range of 95-100%. Early complications were relatively rare; however, up to 87% of long-term complications were reported. Stent placement is a risk factor for lower respiratory tract infection, an adverse prognostic factor in lung cancer survival. Airway stents should be indicated and used with caution and discretion. With the advancement and development of technology, various materials and types of airway stents are being developed to minimize adverse outcomes.